Validation Study of the Method of Analysis of Fe (II) Levels in Blood Addition Tablet Preparations by Wet Destruction and Dry Destruction Methods by UV-Vis Spectrophotometry - Nurul Fajar Agustina; Endah Widhihastuti (Universitas Negeri Semarang, 2024)
Iron is one of the micro minerals needed in the human body. One effort to meet iron needs can be done by consuming blood supplement tablets that contain iron. The iron content contained in blood supplement tablets needs to be known by carrying out quality testing to ensure that the preparation contains the specified ingredients and quantities. The UV-Vis spectrophotometer is an alternative method for determining iron levels because it has lower operating costs and is simpler but has high sensitivity. Determining the iron content to be analyzed requires a complexing agent to form colored compounds. The complexing compound often used in this research is phenantorline. The requirement for metal analysis using a UV-Vis Spectrophotometer is that the sample must be in solution form so a digestion process needs to be carried out. Destruction is divided into two, namely dry and wet destruction. This study aims to compare two digestion methods that are commonly used, namely wet digestion and dry digestion in determining Fe (II) levels in blood supplement tablets. In this research, method validation will also be carried out which aims to show that the testing procedures used obtain the expected results consistently and continuously. Validation of analytical methods carried out includes linearity test parameters, detection limit tests, quantitation limit tests, accuracy tests and precision tests. . Linearity is indicated by R2 of 0.9986; detection limit of 1.10 mg/L; quantitation limit of 3.62 mg/L; accuracy of dry digestion and wet digestion between 80-120%; and precision of dry digestion and wet digestion as indicated by an RSD percentage below 2%. Quantitative test results showed that the percentage levels of blood added tablet samples from wet digestion and dry digestion were 91.52% respectively; 100.09%; 96.15%; 100.96%; 100.67%. and 93.39%; 108.29%; 99.47%; 93.47%; and 92.57%.